2021
DOI: 10.26623/themessenger.v13i3.3991
|View full text |Cite
|
Sign up to set email alerts
|

Trump’s Twitter Propaganda During Covid-19

Abstract: <em><span lang="EN-US"><em><span>During the early Covid-19 pandemic, led by controversial presidential figure Donald Trump, the US seemed to be overwhelmed by this microbial creature, proving to be one of the countries with the most Covid-19. Besides health impacts, there are many multi-effects afterward, such as economic, social, political, and so on, that must be faced after this Covid-19 outbreak. Moreover, the US will hold a presidential election in November 2020. This challenge mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We select Twitter because it is a free medium and candidates may utilize it without worrying about running out of resources. A fair playing field, gives Twitter a wealth of information on campaign messaging (Gross & Johnson, 2016 as cited in Muqsith et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We select Twitter because it is a free medium and candidates may utilize it without worrying about running out of resources. A fair playing field, gives Twitter a wealth of information on campaign messaging (Gross & Johnson, 2016 as cited in Muqsith et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…"The economic ramifications of the coronavirus are increasingly likely to weigh heavily on Trump's re-election chances and quite possibly could cost him re-election," said Dan Eberhart, a Republican donor. (Bennet, 2020 as cited in Muqsith et al, 2021) To overcome this obstacle and maintain his presidential election, Trump must focus on how to resolve COVID-19. Making a story on the social media site Twitter is one of the techniques employed.…”
Section: Trump Covid-19 and Racismmentioning
confidence: 99%
“…In the 2021 research, for example, we found that, on average, Indonesians received one fake news a week as much as 41 %, one fake news in one month as much as 29 %, one news in one day as much as 21 %, and more than one fake news in one month. Day by 9 % (Muqsith, Pratomo, 2021: 1391-1406.…”
Section: Digital Data Manipulationmentioning
confidence: 99%
“…The presence of a large amount of unclear, ambiguous, and inaccurate information during Covid-19 has contributed to an excess of confusing and contradictory information in the online media which has accelerated health anxiety and Covid-19 misinformation sharing (Laato et al, 2020;World Health Organization, 2021) Experts argue that reliance on misinformation related to Covid-19 fuels negligence in prevention and a reluctance to take protective measures, which in turn leads to an increase in the threat of serious illness or even death (Barua et al, 2020). Along with health repercussions, the Covid-19 pandemic will have a number of secondary effects that must be dealt with, including economic, social, and political ones (Muqsith et al, 2021). Since 2019, during the Covid-19 Pandemic, it is necessary to apply appropriate communication strategies (Isnawijayani et al, 2022) Because people often tend to expose themselves to affirmative information and selectively share Covid-19 information based on their attitudes and beliefs (Pennycook et al, 2018), a fundamental prevention of the spread of the infodemic is one way to reduce the ongoing exposure to misinformation which corrupts one's knowledge and beliefs (Kümpel et al, 2015;Vicol, 2020).…”
Section: Introductionmentioning
confidence: 99%